Oncolytic virus expressing PD-1 inhibitors activates a collaborative intratumoral immune response to control tumor and synergizes with CTLA-4 or TIM-3 blockade. Issue 6 (10th June 2022) - Ju, Fei; Luo, Yong; Lin, Chaolong; Jia, Xian; Xu, Zilong; Tian, Rui; Lin, Yanhua; Zhao, Min; Chang, Yating; Huang, Xiaoxuan; Li, Shaopeng; Ren, Wenfeng; et al.
Abstract : Background: Oncolytic viruses (OVs) are capable to inflame the tumor microenvironment (TME) and elicit infiltrating tumor-specific T cell responses. However, OV treatment negatively alters the cancer-immune set point in tumors to attenuate the antitumor immune response, which suggests the necessity of dissecting the immune landscape of the virus-treated tumors and developing novel strategies to maximize the potential of OVs. The aim of this study is to investigate the effect of the single-chain variable fragment (scFv)-armed OVs targeting PD-1 on the TME, and ultimately overcome localized immunosuppression to sensitize tumors to immunotherapies. Methods: A tumor-selective oncolytic herpes simplex virus vector was engineered to encode a humanized scFv against human PD-1 (hPD-1scFv) (YST-OVH). The antitumor efficacy of YST-OVH was explored in multiple therapeutic mouse models. The neurotoxicity and safety of YST-OVH were evaluated in nonhuman primates. The precise dynamics in the TME involved in YST-OVH treatment were dissected using cytometry by time-of-flight (CyTOF). Results: The identified hPD-1scFv showed superior T-cell activating activity. Localized delivery of hPD-1scFv by YST-OVH promotes systemic antitumor immunity in humanized PD-1 mouse models of established cancer. Immune profiling of tumors using CyTOF revealed the enhanced antitumor effect of YST-OVH, which largely relied on CD8 + T cell activity by augmenting the tumor infiltration of effector CD8 + T cells and establishment of memory CD8 + T cells and reducing associated CD8 + T cell exhaustion. Furthermore, YST-OVH treatment modified the cancer-immune set point of tumors coupled to coexpression of CTLA-4 and TIM-3 on exhausted CD8 + T cells and high levels of CTLA-4 + Treg cells. A combination approach incorporating anti-CTLA-4 or anti-TIM-3 further improved efficacy by increasing tumor immunogenicity and activating antitumor adaptive immune responses. Moreover, this therapeutic strategy showed no neurotoxicity and was well tolerated in nonhuman primates. The benefit of intratumoral hPD-1scFv expression was also observed in humanized mice bearing human cancer cells. Conclusion: Localized delivery of PD-1 inhibitors by engineered YST-OVH was a highly effective and safe strategy for cancer immunotherapy. YST-OVH also synergized with CTLA-4 or TIM-3 blockade to enhance the immune response to cancer. These data provide a strong rationale for further clinical evaluation of this novel therapeutic approach.